Analisis Pemahaman Matematika Mengenal Lambang dan Nama Bilangan Menggunakan Media (LABER) Lagu Berhitung Kelas I Sekolah Dasar: Analisis Pemahaman Matematika Mengenal Lambang dan Nama Bilangan - Aryani, Defitri Maretika (FKIP, PGSD, Universitas Slamet Riyadi, 2024)
This study aims to determine the understanding of students in learning mathematics using song media (LABER) in Class I Counting Songs with the material of symbols and number names in elementary schools. This research uses a problem-based learning model. The type of data in this study uses qualitative data. The instruments in the study were interviews and observations. So in this study, it can be concluded that out of 20 students, there are 63% (3) who still do not understand the material about recognizing symbols and number names. Based on the results of the study and discussion, the researcher can conclude that the development of math learning songs has successfully produced a product with the material of recognizing symbols and number names using song media (LABER) counting songs for grade I students.